2016
DOI: 10.1080/07391102.2016.1194230
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of carnosine on dehydroascorbate-induced structural alteration and opacity of lens crystallins: important implications of carnosine pleiotropic functions to combat cataractogenesis

Abstract: The high level of dehydroascorbic acid (DHA) in the lenticular tissue is an important risk factor for the development of age-related cataracts. In this study, the effects of DHA on structure and function of lens crystallins were studied in the presence of carnosine using gel mobility shift assay, different spectroscopic techniques, and lens culture analysis. The DHA-induced unfolding and aggregation of lens proteins were largely prevented by this endogenous dipeptide. The ability of carnosine to preserve nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
0
8
0
1
Order By: Relevance
“…The levels of these reactive species increased in a dose-dependent manner by Aβ1-42 oligomers, whereas they significantly diminished in the presence of carnosine (Figure 2 and Figure 3) in accordance to its antioxidant activity and the ability of this peptide to directly interact with these species, decreasing their availability [6,76]. In particular, part of the observed decreased toxicity could be due to an increased uptake of carnosine by immune cells under stress conditions [77], to the ability of this dipeptide to convert NO into its not-toxic end-product nitrite [6], and/or carnosine capability to disassemble aggregate structures already formed [78,79]. In accordance to the viability and NO and O 2 −• results, Figure 4A–C shows that the decrease in reactive species depends not only on the scavenging activity of carnosine [80] but also on the ability of this peptide to decrease the expression Aβ-induced enzymes related to oxidative and nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of these reactive species increased in a dose-dependent manner by Aβ1-42 oligomers, whereas they significantly diminished in the presence of carnosine (Figure 2 and Figure 3) in accordance to its antioxidant activity and the ability of this peptide to directly interact with these species, decreasing their availability [6,76]. In particular, part of the observed decreased toxicity could be due to an increased uptake of carnosine by immune cells under stress conditions [77], to the ability of this dipeptide to convert NO into its not-toxic end-product nitrite [6], and/or carnosine capability to disassemble aggregate structures already formed [78,79]. In accordance to the viability and NO and O 2 −• results, Figure 4A–C shows that the decrease in reactive species depends not only on the scavenging activity of carnosine [80] but also on the ability of this peptide to decrease the expression Aβ-induced enzymes related to oxidative and nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%
“…(co-inc.) treatments, the latter gave always slightly stronger effects. The increased protective effect observed with carnosine in microglial cells after the co-incubation of Aβ monomers with a millimolar concentration of carnosine suggests that the anti-aggregation properties of carnosine [5,78,79] significantly contribute to increase the overall protective effects of carnosine against Aβ1-42 toxicity in addition to the antioxidant activity of this peptide. Furthermore, our data obtained with AFM suggest that carnosine might preserve Aβ monomers, which are essential for neuronal survival and maintaining neuronal glucose homeostasis [84,85], and it can also promote the dissociation of Aβ oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine has been described as having a hypoglycemic effect, an indirect intracellular antioxidant activity, anti-inflammatory properties and carbonyl-trapping capacities [ 71 ]. Naturally present in significant concentrations in the human lens, it was successfully tested as an antiglycation agent for the lens with the aim of delaying senile cataracts [ 72 , 73 ]. Retarding the tissue accumulation of AGEs with carnosine or certain derivatives of this dipeptide should be investigated further.…”
Section: Inhibition Of Glycation With Isolated Products From Foodsmentioning
confidence: 99%
“…Carnosine has been revealed to be an effective scavenger for the removal of reactive carbonyl species, as determined in a mouse model of diabetic nephropathy, and the reactive species located in pancreatic β-cells (10,14). Javadi et al (15) demonstrated that carnosine primarily prevents dehydroascorbic acid-induced unfolding and the aggregation of lens proteins and significant lens opacity. Furthermore, other studies have revealed that carnosine exerts a positive effect on the prevention and treatment of DR, but it has no association with anti-oxidation and anti-glycosylation (16,17).…”
Section: Introductionmentioning
confidence: 99%